(untitled) (Colombia Medica, 1993)
Hemodynamic evaluation in critically ill patients evaluates blood pressure and provides data on volume, blood flow, and the forces involved in the cardiovascular system. This paper informs in a sequential and logical form both nomenclature and definitions of the cardiovascular system along with the mathematical formulae required in the hemodynamic analysis of critically ill patients at the intensive care unit. Thus, it is possible to know and measure the following values: preload, post-load, cardiac contractility, and cardiac output, as well as oxygen delivery and uptake by peri tissues through systemic perfusion.